The birth of the Yoruba hegemony in post-abolition candomblé - Luis Nicolau Parés (Journal de la Société des Américanistes)
The birth of the Yoruba hegemony in post-abolition candomblé. Historical data indicates that critical Jeje and Nagô religious practices of West African origin were already well consolidated in Salvador (Bahia, Brazil) in the 1860s, suggesting their rooting in the period of the slave-trade. While the Yoruba ethnogenesis and the racial and cultural nationalism of the « Lagosian Renaissance » in the 1890s may have indirectly contributed to the late 19th century Bahian « Nagôization » of candomblé, the paper suggests that the increasing religious predominance of the Nagô « nation » was mainly the result of competitive local Creole micro-politics.